Does the type of disability influence salivary cortisol concentrations of athletes in official wheelchair basketball games?. Issue 4 (August 2019) - Seron, Bruna Barboza; Carvalho, Emanuel Messias Oliveira de; Modesto, Everaldo Lambert; Almeida, Eloise Werle de; Moraes, Solange Marta Franzói de; Greguol, Márcia
The objective of this work is to describe and compare the behavior of cortisol in official wheelchair basketball matches according to the type of disability. This is a cross-sectional study in which 34 elite wheelchair basketball athletes were divided into three groups, based on disability (spinal cord injury, poliomyelitis, and amputation). Cortisol concentration (baseline, pre-, and post-game) and heart rate were analyzed in five official games. Heart rate data were stratified according to the Edwards method. Significant differences were observed in pre- and post-cortisol concentrations only for the amputated group. No significant correlations were found between cortisol variation and intensity ranges. Athletes with neurological damage were not responsive to wheelchair basketball in relation to salivary cortisol concentrations. The game intensity cannot be verified by the biomarker cortisol for all types of disabilities. It is necessary to pay attention to the energy availability for athletes with neurological injuries during the game and post-game recovery.